Planning in Islamic Education Management: A Study of Irfani's Epistemological Perspective - Nurhadi Nurhadi; Masyitoh Masyitoh; Agus Suradika; Saiful Bahri (PT Publikasiku Academic Solution, 2025)
This study aims to examine planning management in Islamic education with the perspective of Irfani's epistemology, which emphasizes the spiritual and intuitive dimension in the educational process. This approach is integrated with the epistemology of Bayani and Burhani as initiated by Muhammad Abed Al-Jabiri, to create a holistic and comprehensive education system. This research uses a qualitative method with documentation-based data collection techniques and in-depth interpretation of Al-Jabiri's main works, such as Takwin al-'Aql al-'Arabi, as well as other supporting literature. Data analysis is carried out through data reduction, data presentation, and drawing conclusions using an interpretive and holistic approach. The results of the study show that planning in Islamic education management based on Irfani's epistemology emphasizes the depth of spirituality, which is complemented by Bayani's normative foundation and Burhani's rational analysis. Irfani's approach encourages inner experience, contemplation, and transcendental relationships with God, which provides a balanced dimension between the mundane and ukhrawi aspects in educational planning. The discussion also found that this approach can strengthen the vision and mission of Islamic education in building the character of kamil people who are integrity, intellectually intelligent, and morally and spiritually responsible. In conclusion, the integration of these three epistemologies, in particular with an emphasis on the Irfani perspective, offers a holistic planning framework, making Islamic education more relevant and adaptive to the challenges of the times, without neglecting the spiritual values and morality that are its essence.